2020
DOI: 10.18632/oncotarget.27424
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium perfringens enterotoxin induces claudin-4 to activate YAP in oral squamous cell carcinomas

Abstract: Claudin (CLDN)-4 expression has been associated with malignancy in various cancers. When CLDN4 expression was examined in oral squamous cell carcinoma (OSCC), 22 out of 57 (39%) cases showed immunoreactivity in the nucleus. Nuclear CLDN4-positive cases showed a stronger correlation with cancer progression than the negative cases. Intratumoral anaerobic bacterial DNA examination revealed nuclear CLDN4 expression in 81% of Clostridium perfringens-positive cases. Treatment of human oral squamous cell carcinoma ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 56 publications
3
30
0
Order By: Relevance
“…In our analysis of CRC patients, CPE was also detected in patients receiving long-term administration of PPI. We previously reported that CPE produced by C. perfringens impairs CLDN4, which forms tight junctions, to promote cancer progression by activating YAP [19]. Consistent with this, in the present study, CPE activated YAP to enhance the expression of cyclin D1 and NS, which are target genes of YAP.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In our analysis of CRC patients, CPE was also detected in patients receiving long-term administration of PPI. We previously reported that CPE produced by C. perfringens impairs CLDN4, which forms tight junctions, to promote cancer progression by activating YAP [19]. Consistent with this, in the present study, CPE activated YAP to enhance the expression of cyclin D1 and NS, which are target genes of YAP.…”
Section: Discussionsupporting
confidence: 91%
“…Bacterial DNA detection by PCR was performed as previously described [19]. Bacterial DNA was extracted from the CRC specimens (10 thin-sliced paraffin-embedded tumor specimens, deparaffinized and hydrated) using the QIAamp DNA mini kit (Qiagen, GmbH, Hilden, Germany) according to the manufacturer's instructions.…”
Section: Bacterial Dna Amplificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-membranous CLDN4 localization is reported to be mediated by CPE [18]. Therefore, we examined CPE gene expression in the adenoma tissues ( Figure 3A).…”
Section: Effect Of Cpe On Colon Epithelial Cellsmentioning
confidence: 99%
“…High concentration of c-terminus of CPE binds to second extracellular loop of CLDN4 to destruct homotipic claudin bindings of the tight junction to provide diarrhea [16]. In contrast, we have reported that impairment of tight junction by low concentration of CPE leads to activation of YAP by internalization of CLDN4 in oral squamous cell carcinoma (OSCC) [18]. In the present study, we investigated whether such CPE-mediated activation of YAP is involved in the malignant progression of SSA/P and malignant phenotype of CRC, which findings might be expected to provide prevention of CRC.…”
Section: Introductionmentioning
confidence: 99%